Komunikasi Verbal Body Shaming di Media Sosial Twitter terhadap Kepercayaan Diri Remaja - Shavira Shavira; Roswita Oktavianti (Kiwari, 2023)
Bullying of body shaming is increasingly prevalent on Twitter. With the existence of social media, bullying often occurs in cyberspace. Verbal communication is communication that is carried out orally or in writing. Verbal communication on Twitter uses writing. Body shaming is bullying that targets body shape, skin color, and body hair. Meanwhile, what is meant by self-confidence is a strong feeling of trust in one's own abilities. The purpose of this study was to find out if there was any influence of verbal body shaming communication on Twitter social media on adolescent self-confidence. The independent variable in this study is verbal communication and the dependent variable is self-confidence. The approach used for this research is a quantitative approach using a questionnaire method that is spread on social media Twitter. The results of this study show that there is no influence between verbal communication on Twitter social media and adolescent self-confidence. Usually, the perpetrator of body shaming only sees from 1 post that does not represent the overall state of the victim. There are also not a few Twitter users who use pseudonymous identities. What's more, Twitter is limited to 240 characters per tweet. Perundungan (bully) body shaming semakin marak di Twitter. Dengan adanya media sosial, perundungan sering terjadi di dunia maya. Komunikasi verbal merupakan komunikasi yang dilakukan secara lisan maupun tulisan. Komunikasi verbal di Twitter menggunakan tulisan. Body shaming merupakan perundungan yang menargetkan bentuk tubuh, warna kulit, dan rambut tubuh. Sedangkan yang dimaksud dengan kepercayaan diri adalah perasaan percaya yang kuat terhadap kemampuan diri sendiri. Tujuan dari penelitian ini adalah untuk mengetahui apakah ada pengaruh komunikasi verbal body shaming di media sosial Twitter terhadap kepercayaan diri remaja. Variabel independen dalam penelitian ini adalah komunikasi verbal dan variabel dependennya adalah kepercayaan diri. Pendekatan yang digunakan untuk penelitian ini adalah pendekatan kuantitatif dengan menggunakan metode kuesioner yang disebarkan di media sosial Twitter. Hasil penelitian ini menunjukkan bahwa tidak ada pengaruh antara komunikasi verbal di media sosial Twitter dengan kepercayaan diri remaja. Biasanya, pelaku body shaming hanya melihat dari 1 unggahan yang tidak mewakili keadaan korban secara keseluruhan. Juga tidak sedikit pengguna Twitter yang menggunakan identitas samaran. Terlebih, Twitter dibatasi hanya 240 karakter setiap tweetnya.